Formulation of Governance and Democracy Index (GDI) and Governance, Democracy, and Emancipation Index (GDEI): A Cross-country Empirical Study (1998 – 2017) - Roy Debasish (De Gruyter, 2020)
This research paper is aimed at formulation of a composite Governance and Democracy Index (GDI) based on the six indicators of good governance by Kaufmann et al. (2003, 2007) to assess and evaluate the relative performances of 10 major democracies of the world for the time period of 20 years (1998 – 2017) (Base Year = 1996). In order to do so, three distinct methodologies are adopted based on the absolute values and relative changes in the observations of independent variables. The extended part of this research involves formulation of Governance, Democracy, and Emancipation Index (GDEI) which incorporates the Emancipative values.